Arquitectura infraestructural habitacional para la tercera y la cuarta revolución industrial - Costa, Leandro Tomás (2022)
Two theories arise as a solution to an environmental environment in crisis and as proposals in the face of the early scarcity of energy and material resources, these are the Third Industrial Revolution and the Fourth Industrial Revolution. Both have in common the development of complementary advanced strategies for the development of a cyber society, as a New Technical Regime distributed on the planet, which will implicitly carry the problems of global overpopulation and total control of subjects, things and energies, through physical and metaphysical information infrastructures, infrastructures such as true mazes of pure interiority that will be the nebulous domain from which an inevitably infraestructural housing architecture should be projected, sustained. From a critical reading on the theories of the Third and Fourth Industrial Revolution, an interpretation of this context is made, with the aim of proposing projectural statements. From the experimental practice with the corresponding statements, and as verification thereof, it will be a new proposal for the City of Buenos Aires as the basis of a third gender of the project that integrates a new dimension of the urban and the value of architecture as a qualifier of the habitat.